The Nurses’ Role in Providing Comfort During Childbirth Using Ambulation and Hydrotherapy (International Journal of Studies in Nursing, 2018)
Providing care and comfort to women during childbirth is an important role. While medical interventions are available, all are associated with potential risks. Using nonpharmacologic means to support the normal process of birth, nurses may reduce the use of medical procedures and their potential complications. The purpose of this article is to discuss the use of two techniques that promote physiologic childbirth, ambulation and hydrotherapy, and the nurses’ role in providing comfort using these techniques in this important life event. Use of these techniques may delay or minimize the use of medical interventions while supporting the normal physiology of labor and birth.